Transparent rules for deposing central bankers - Arayssi, Mahmoud (2015)
I model flexible targeting with linear and quadratic loss function in the output gap and inflation rate. I find a form of targeting with one-sided dismissal rules attractive; it discourages the central banker from inflating and minimizes the probability of its dismissal in the presence of aggregate supply shocks. This procedure ties the central banker's performance to observable policy targets, whether the nominal output or the inflation rate, and gives some valuable flexibility in terms of stabilization of shocks Two cases of targeting procedures, nominal output targeting and inflation targeting, are compared to the full discretionary case without any dismissal rule. The central banker, accountable to hit the policy target, implements a dominant policy whenever she takes a hawkish stance against inflation, and targets the variable that is most affected by the unobservable supply shock. This type of reappointment contract implies that monetary policy would become fully transparent, consistently more credible and more effective than the discretionary case without dismissal.